The protective performance of selected UK police body armor challenged by M75 grenades - Cahill, Keith; Booth, Michael; Mercer, Jamie; Sabha, Anmar; Carr, Debra J.; Malbon, Christopher (International Ballistics Society, 2017)
UK Police ‘soft’ body armor is designed to provide protection from sharp-weapons and low-velocity pistol ammunition; if ‘hard’ armor plates are fitted then high-velocity rifle protection is provided. Several different levels of protection for both soft and hard armor are available and these are tailored to the individual police officers’ role. The level of protection offered by these types of armor from fragmentation threats is not known as fragmentation is not typically considered a threat to UK Police Officers. However, fragmentation from devices such as grenades may be a threat to certain specialized units and during terrorist incidents. In this work, neither the soft nor hard UK Police body armor (HG2 and RF1 respectively) investigated were perforated when challenged by M75 Yugoslavian grenades at a distance of 1 m from the point of detonation. The effect due to blast was not considered. The work has provided confidence regarding the performance of selected police body armor against fragmentation from a selected grenade threat.